Promoting Ethics and Integrity in Management Academic Research: Retraction Initiative - Ayodele, Freida Ozavize; Liu, Yao; Hasnah, Haron (Universiti Malaysia Pahang, 2017)
In management academic research, academic advancement, job security, and securing of research funds in the university are judged mainly by the outputs of publications in high impact journals. With bogus resume filled with published journal articles, the university and other allied institutions are keen to recruit or sustain the appointment of such academics. This often leads to undue pressure on the parts of the intending academics or those already recruited to engage in research misconducts. This structured review therefore focuses on the ethics and integrity issues in management research via the analysis of retracted articles within a period of 2005-2016. This study employs a literature review methodology. In 2017, the database (Crossref and Google scholar) of retracted articles published between 2005 and 2016 in the field of management science were searched by using Boolean strings such as retracted articles in management, notice of retraction in management science, research ethics, and plagiarism in management research. The searched articles were subsequently streamlined by choosing the articles based on their relevance and content in accordance with the inclusion criteria. Based on the analyzed retracted articles, the study shows that there are evidences of unethical issues among researchers in management science. The unethical issues identifies include data falsification, duplication of submitted articles, plagiarism, data irregularities and incomplete citations. Interestingly, the analyzed results indicate that knowledge management has the highest number of retracted articles with plagiarism as the predominant ethical issues. Also, the findings from this study indicated that unethical misconducts are not restricted to a particular geographical location but cut across different countries. However, it is moreprevalent in some countries compare to others.